Bone Indices in Thyroidectomized Patients on Long-Term Substitution Therapy with Levothyroxine Assessed by DXA and HR-pQCT. (13th July 2015) - Moser, Emil; Sikjaer, Tanja; Mosekilde, Leif; Rejnmark, Lars
Abstract : Background . Studies on bone effects of long-term substitution therapy with levothyroxine (LT4 ) have shown discrepant results. Previous studies have, however, not evaluated volumetric bone mineral densities (vBMD), bone structure, and strength using high resolution peripheral quantitative computed tomography (HR-pQCT) and finite element analysis (FEA). Using a cross-sectional design, we aimed to determine whether BMD, structure, and strength are affected in hypothyroid patients on LT4 substitution therapy. Methods . We compared 49 patients with well-substituted hypothyroidism with 49 age- and gender-matched population based controls. Areal BMD was assessed by DXA, vBMD and bone geometry by HR-pQCT, and bone strength by FEA. Results . Patients had been thyroidectomized due to thyroid cancer (10%) and nontoxic (33%) or toxic goiter (57%). 82% were women. TSH levels did not differ between groups, but patients had significantly higher levels of T4 (p < 0.001 ) and lower levels of T3 (p < 0.01 ). Compared to controls, patients had higher levels of magnesium (p < 0.05 ), whereas ionized calcium and PTH were lower (p < 0.05 ). Bone scans did not reveal any differences in BMD, bone geometry, or strength. Conclusion . If patients with hypothyroidism are well-substituted with LT4, the disease does not affect bone indices to any major degree.